Clinico-etiological and histopathological correlation in erythroderma: In a tertiary care hospital of Eastern Odisha - Dharmendra Kumar Sahu ,; Purna Chandra Singh,; Jayashree Mohanty,; Dharma Niranjan Mishra, (Asian Journal of Medical Sciences, 2023)
Background: Erythroderma, or “exfoliative dermatitis,” is a generalized inflammatory disorder of the skin manifesting with erythema and scaling affecting more than 90% of the skin surface. Primary erythroderma develops in normal skin, and etiological factors include drug reaction, lymphomas, and hematological malignancies, which may be idiopathic. Aims and Objectives: The present study is to evaluate the clinico-etiological and histopathological correlations in erythroderma. Materials and Methods: This prospective observational study was done in the Department of Dermatology, S.C.B. Medical College, Cuttack, from 2021 to 2022. Erythema and scaling involving more than 90% of the body surface area were calculated by Wallace’s rule of nine. A detailed demographic profile and history were recorded with a thorough clinical examination for each patient, involving type of scales, sizes of scales, color of scales, associated lichenification or fissuring, pedal edema, examination of the scalp for scales, hair loss, examination of the nails and mucosa, and associated arthritis. Results: The most common disease was psoriasis (16), Idiopathic (7), followed by atopic and drug-induced dermatitis 6 patients each. Seborrheic dermatitis showed 3 cases, followed by contact dermatitis, Reiter’s disease, Pemphigus foliaceus, Ichthyosis (congenital), Dermatomyositis, and malignancy-induced 2 cases each, whereas contact dermatitis and Dermatophyte infection were found to be one patient each. Conclusion: Though some of the etiology remains unknown, repeated investigations and continued follow-up are necessary to determine long-term complications. The role of alternative medicines and the injudicious use of steroids by quacks or untrained practitioners should be discouraged, and proper awareness should be given to patients with erythroderma.